Exiles, entrepreneurs, and educators : African Americans in Ghana - Taylor, Steven J. L., 1958- (SUNY series in African American studies., 2019)
After repeated coups and periods of military rule, Ghana is now one of Africa's longest enduring democratic republics. Exiles, Entrepreneurs and Educators compares the political proclivities of two generations of African Americans who moved to Ghana. Author Steven J.L. Taylor blends archival and ethnographic research, including interviews, to provide a unique perspective on these immigrants who chose to leave an economically developed country and settled in an impoverished developing country. The first generation consisted of voluntary exiles from the US who arrived from 1957 to 1966, during the regime of President Kwame Nkrumah, embracing both Nkrumah and his left-leaning political party. In contrast to the first, many in the second generation left the US to establish commercial enterprises in Ghana. Although they identified with the Democratic Party while living in the US, and were politically active, this second generation has for the most part avoided political activity in Ghana while identifying with the Ghanaian party that is modeled after the Republican Party in the US. Taylor helps to dispel some of the incorrect assumptions about African politics and provides readers with an insightful look at how developing nations can embark upon a path toward democratization.--Provided by publisher.